Simulation study on lens manufacturing process flow - Olugu, Ezutah Udoncy; Wong, Kuan Yew (IEEE Computer Society, 2008)
The general question addressed by this work is how best productivity can be enhanced in the process flow of a lens manufacturing company without incurring any major extra cost. Process analysis has been conducted in the process flow of the firm in order to identify improvement prone areas and improvement alternative solutions were proposed. The application of discrete event simulation using WITNESS software has been employed in the evaluation of the production improvement solutions in order to identify which alternative solution yields the highest productivity. Generic performance measures and specific organizational performance measures has been investigated to provide subtle insights into the perceived benefits of adopting alternative manufacturing process structures in the process flow using simulation.